Is maternal SARS-CoV-2 infection in the first trimester associated with congenital heart defects? - Athina Samara; Athina Samara; Athina Samara; Conrado Milani Coutinho; Paul T. Heath; Asma Khalil; Asma Khalil; Asma Khalil (Frontiers in Pediatrics)
Emerging evidence suggests a potential link between maternal SARS-CoV-2 infection during early pregnancy and the development of congenital heart defects (CHD) in offspring. Although vertical transmission of SARS-CoV-2 is rare, the virus has been associated with placental complications and increased maternal morbidity. Recent studies from China report increased rates of CHD and anomalies such as situs inversus when infection occurs during gestational weeks 4–6, a critical window for cardiac development. Additional reports from different parts of the world also highlight post-pandemic increases in specific cardiac anomalies, including ventricular septal defects (VSDs). Multiple mechanisms may underlie these associations. SARS-CoV-2 can induce placental inflammation, compromise the cytotrophoblast barrier, and impair nutrient and gas exchange, potentially leading to fetal hypoxia and disrupted morphogenic signalling. Furthermore, maternal inflammation and elevated cytokines, along with viral effects on ACE2-expressing fetal cardiac progenitors, could further affect proliferation, differentiation, and apoptosis during cardiac development. Co-infections, hormone disruption, and maternal stress could also contribute. There is an urgent need for longitudinal studies with comprehensive maternal-fetal data, including infection timing, vaccine status, and biological sampling. These will be essential to delineate the multifactorial impacts of maternal infection on fetal cardiac development and long-term outcomes. Special focus should be placed on infections during early pregnancy (weeks 4–7), the period of cardiac septation and left-right asymmetry establishment, to determine causality and inform prevention strategies.